Konsep Pendidikan Karakter Menurut KH. Abdurrahman Wahid - Sri Wargiani; Zulfa Khoirun Nissa; Ilhami Nurisfa Pratami; Putut Ardianto; Saiful Arifin; Muhammad Sholihin (IJoIS: Indonesian Journal of Islamic Studies, 2023)
This study aims to determine Gus Dur's views on character education. This research is a research with library research method. The analysis technique used to solve a problem is based on some relevant literature or has anything to do with the problem under study. The results of the study show that Gus Dur has a concept of character education that promotes morality in the administration of education. Character education in question is oriented towards the formation of personality and noble character based on the Al-Qur'an and al-Hadith, as well as to seek the values ​​of tolerance. Gus Dur's Islamic education is centered on guiding students to become individuals who are free, self-aware, independent, and free from barriers that impede human rights. Islamic education from Gus Dur's perspective must also be able to face the challenges of the globalization era and not be limited to conventional methods. In addition, Gus Dur paid attention to pluralism education. He wanted to reform public schools and Islamic boarding schools to empower Muslims.